Representasi Konsep Uchi-Soto pada Penerjemahan Teineigo dalam Subtitle Drama Jepang - Salsabila, Dhia Ardhina; Hariri, Tatang (IZUMI, 2023)
This study uses a qualitative descriptive method to analyze the representation of the uchi-soto concept as a form of teineigo in Japanese and its translation into Indonesian. The uchi soto concept as an in-group and out-group concept has a very strong influence on language in Japanese society. This study aims to find out how the concept of uchi soto is represented as a form of honorific, to analyze the form of teienigo translation and changes in meaning that occur in the translation. The results of the study shown that the concept of soto is more often used in the -masu form while the concept of uchi is more often used in the -desu form. Translation results contained in the drama subtitles of The Journalist (2022) and Pretty Proofreader (2015) shown that there are several changes in meaning made by the translator. This is caused by the different translators in each drama and translator's lack of understanding of these two concepts. The analysis of the form of honorific translation illustrates the complexity of the translation process which affects the equivalence of the translation. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor